Preparation method of hierarchical porous wood aerogel-based electrode material

By performing sodium chlorite delignification and heat treatment on the wood, combined with in-situ polymerization technology, a graded porous wood aerogel-based electrode material is prepared, which solves the problems of wood-based electrode materials prone to cracking, warping and collapse in the prior art, and achieves high-performance electrode material preparation.

CN114864296BActive Publication Date: 2025-05-02NANJING FORESTRY UNIV +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202210605608.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-05-31
Publication Date
2025-05-02
Estimated Expiration
2042-05-31

AI Technical Summary

Technical Problem

In the prior art, when preparing wood-based electrode materials, high-temperature carbonization treatment leads to the material being prone to cracking, warping and collapse, and has high energy consumption and complex process, making it difficult to form a continuous conductive network structure, affecting electron transfer and the circulation and storage of electrolyte ions.

Method used

By cutting the wood into thin slices along the cross-section, sodium chlorite delignin treatment and heat treatment, lignin and hemicellulose are removed to form a graded porous structure. Then in situ polymerization is carried out in pyrrole monomer or aniline monomer, or carbon nanotubes, graphene or metal nanoparticles are added for polymerization, to prepare a graded porous wood aerogel-based electrode material with excellent electrochemical properties.

Benefits of technology

The internal structure of the wood is optimized, the porosity and specific surface area are significantly improved, and the continuous conductive network structure is formed, the electron transport and permeation and storage capacity of electrolyte ions are improved, and the specific capacitance and power density of the electrode material are improved.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a method for preparing a hierarchical porous wood aerogel-based electrode material, which comprises cutting wood into thin wood chips along a cross section and drying the wood chips uniformly; vacuum impregnating the wood chips in an acidic sodium chlorite solution to remove lignin in the wood chips by reaction, freezing the wood chips with liquid nitrogen, and freeze drying the wood chips; heat treating the wood chips to remove hemicellulose, and then immersing the wood chips in an acetic acid solution, freezing the wood chips with liquid nitrogen, and freeze drying the wood chips; and then using ferric chloride as an oxidant in a pyrrole monomer to perform in-situ polymerization to prepare a hierarchical porous wood aerogel-based electrode material; or impregnating the wood chips in an aniline monomer, and using hydrochloric acid as a dopant to perform in-situ polymerization to prepare a hierarchical porous wood aerogel-based electrode material. The invention can prepare a hierarchical porous wood aerogel-based electrode material with excellent electrochemical performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of electrode materials and relates to a method for preparing a graded porous wood aerogel-based electrode material. Background Art

[0002] In recent years, the research on biomass electrode materials has gradually become a hot topic. Wood has become one of the preferred electrode substrates due to its natural hierarchical porous materials. At present, in order to make full use of the porosity, biodegradability and sustainability of wood, relevant researchers have directly delignified or high-temperature carbonized large pieces of wood to prepare wood / wood carbon-based electrode materials. However, only through delignification treatment, due to the high content of lignin in the wood intercellular layer and cell corners, it is easy to be removed, and the macroporous structure is significantly increased; but due to the low lignin content in the cell wall structure, it still shows a compact cell wall structure, which makes it difficult for semiconductor polymers or conductive materials to enter the cell wall to form a continuous conductive network structure. At the same time, the micro-nano pore structure has not been significantly improved, which is not conducive to the transfer of electrons and the circulation and storage of electrolyte ions. After high-temperature carbonization treatment, the wood carbon-based electrode material has excellent electrochemical performance due to the increase in conductivity and the significant increase in the specific surface area of ​​the micro / nano pore structure. Then, as a non-homogeneous biomass material, wood shrinks differently in the tangential, tangential and radial directions during high-temperature carbonization, which makes it easy for the wood to crack, warp and collapse. At the same time, high-temperature heat treatment consumes a lot of energy and the preparation process is relatively complicated. Therefore, it is very important to have a high-performance preparation method for wood-based electrode materials. Summary of the invention

[0003] The purpose of the present invention is to provide a method for preparing a hierarchical porous wood aerogel-based electrode material.

[0004] The technical solution of the present invention:

[0005] A method for preparing a hierarchical porous wood aerogel-based electrode material, the steps comprising:

[0006] (1) Cut the wood into wood chips with a thickness of 1 to 4 mm along the cross section and dry them evenly to a moisture content of 6 to 8%;

[0007] (2) Vacuum immersing the dried wood chips in an acidic sodium chlorite solution to remove lignin from the wood chips and washing them to neutrality;

[0008] (3) freezing the cleaned and neutralized wood chips with liquid nitrogen and then freeze-drying them;

[0009] (4) heat treating the freeze-dried wood chips at 160-200°C for 2-6 hours to remove hemicellulose in the wood chips, then directly soaking them in an acetic acid solution to remove the soluble sugars remaining after the pyrolysis of the hemicellulose, and washing them to neutrality;

[0010] (5) freezing the wood chips with liquid nitrogen again and then freeze-drying them to produce a hierarchical porous wood aerogel material;

[0011] (6) The freeze-dried wood aerogel material is in situ polymerized in pyrrole monomer using ferric chloride as an oxidant to prepare a graded porous wood aerogel-based electrode material; or the freeze-dried wood aerogel material is immersed in aniline monomer and in situ polymerized using hydrochloric acid as a dopant to prepare a graded porous wood aerogel-based electrode material; or carbon nanotubes, graphene or metal nanoparticles are added to the wood aerogel material and then polypyrrole or polyaniline is in situ polymerized to prepare a capacitor electrode material.

[0012] Preferably, in step (1), after the wood chips are dried, they are placed in a climate chamber at a temperature of 25° C. and a relative humidity of 65% for equilibrium treatment.

[0013] Preferably, step (2) is to vacuum immerse the dried wood chips in a sodium chlorite solution with a pH of 4.5-5 and a mass fraction of 4-8%, heat the solution to 70-80°C in a water bath device, react for 40-60 minutes, replace with fresh solution, repeat this process 6-8 times, and wash with deionized water until the pH value reaches neutral after the reaction to remove lignin in the wood chips.

[0014] Preferably, in steps (3) and (5), the liquid nitrogen freezing time is 2 hours and the freeze-drying time is 24 hours.

[0015] Preferably, step (4) comprises placing the freeze-dried wood chips in a tubular furnace and heating them under flowing nitrogen protection at 160-200° C. for 2-6 hours to remove hemicellulose in the wood chips, and then directly placing them in a 3-5% acetic acid solution and shaking and washing them at 45-60° C. for 45-60 minutes to remove soluble sugars remaining after pyrolysis of the hemicellulose, taking out the sample, and washing them again with distilled water until they are neutral.

[0016] Preferably, step (6) further comprises: adding carbon nanotubes, graphene or metal nanoparticles to the hierarchical porous wood aerogel-based electrode material to prepare a capacitor electrode material.

[0017] The present invention first cuts the wood into wood chips of a certain thickness along the cross section and uniformly dries the wood chips to a moisture content of 6 to 8%. Then, the dried wood chips are heated with sodium chlorite under acidic conditions to perform delignification treatment, and then freeze-dried with liquid nitrogen and heat-treated to remove hemicellulose in the wood chips. Then, an acetic acid solution is used to remove the soluble sugars remaining after the hemicellulose is pyrolyzed. The wood chips are washed with distilled water to neutrality and freeze-dried. Finally, polypyrrole is polymerized in situ to obtain a hierarchical porous wood aerogel electrode material. The method first increases the porosity of the wood chips by delignification treatment. Then, the hemicellulose in the wood chips can be removed by heat treatment technology, and the micro / nano pore structure of the wood chips can be further increased, thereby improving the penetration of electrolyte ions and charge storage. At the same time, after heat treatment, the hemicellulose and a small amount of cellulose are degraded in the wood chips to form carbon, which can increase the conductivity of the wood chips. Finally, polypyrrole or polyaniline is polymerized in situ to prepare a hierarchical porous wood aerogel-based electrode material with excellent electrochemical properties.

[0018] By heating the wood with sodium chlorite under acidic conditions, the lignin in the wood is removed, the intercellular layer and cell corners of the wood cell tissue are removed, and then the hemicellulose in the cell wall structure is removed by heat treatment. During the heat treatment process, the hemicellulose is thermally degraded, and the acetic acid formed after the pyrolysis of the hemicellulose can promote the degradation of a small amount of cellulose. Therefore, the cell wall formed has a large number of micro-nano pore structures, forming a hierarchical porous wood aerogel material. This structure provides a more convenient space for the entry of semiconductor polymers and conductive nanoparticles, forming a continuous conductive network structure in the cell wall, which is conducive to the transmission of electrons; at the same time, the formation of this network structure can further improve the micro / nano pore structure of the substrate, providing more transmission channels and storage space for electrolyte ions. On the other hand, the pyrolyzed hemicellulose and a small amount of degraded cellulose exist in the cell wall structure in the form of carbon, which can further improve the conductivity of the wood-based electrode material, and finally form a high-performance hierarchical porous wood aerogel-based electrode material.

[0019] The present invention has the following beneficial effects:

[0020] (I) Breaking through the previous methods of optimizing the internal structure of wood, the paper focuses on the pretreatment of wood. After removing lignin with sodium chlorite under acidic conditions, heat treatment technology is used to degrade the hemicellulose and a small amount of cellulose in the wood cell wall. At this time, the wood has more micro-nano pore structures inside, and the specific surface area of ​​the wood is significantly improved, which is conducive to the in-situ deposition of semiconductor polymers and the entry of conductive nanoparticles, forming a continuous conductive network structure in the cell wall, and improving the transmission path of electrons; at the same time, the formation of this network structure can further improve the micro / nano pore structure of wood aerogel, providing more transmission channels and storage space for electrolyte ions.

[0021] (ii) The pyrolyzed hemicellulose and a small amount of degraded cellulose exist in the cell wall structure in the form of carbon, which can further improve the specific capacitance and power density of the wood-based electrode material, and ultimately form a high-performance hierarchical porous wood aerogel-based electrode material. DETAILED DESCRIPTION

[0022] The technical solution of the present invention is further described below, but is not limited thereto. Any modification or equivalent replacement of the technical solution of the present invention without departing from the spirit and scope of the technical solution of the present invention should be included in the protection scope of the present invention.

[0023] Example 1

[0024] (I) Cut the wood into 1m long squares, and cut them into 2cm (length) × 2cm (width) × 2mm (thickness) wood chips along the cross section. Dry the wood chips at 100℃ until the moisture content is about 6%. Finally, put them in a climate chamber with a temperature of 25℃ and a relative humidity of 65% for equilibrium treatment.

[0025] (ii) Prepare a 5% sodium chlorite solution, add acetic acid dropwise to the solution, adjust the pH of the solution to about 4.5, and stir thoroughly with a magnetic stirrer. Immerse the 2 mm thick wood chips prepared in step (i) in the acidic sodium chlorite solution and heat them in a 70°C water bath for 1 h, then replace with fresh solution, and repeat this process 4 times. After the reaction is completed, wash with deionized water until the pH of the solution is neutral, and dry to a moisture content of 6% to remove lignin from the wood chips.

[0026] (iii) Pour the washed and neutralized wood chips in (ii) into liquid nitrogen and freeze them for two hours. Then put the wood chips frozen with liquid nitrogen into a freeze dryer and vacuum freeze-dry them for 24 hours before taking them out.

[0027] (iv) Place the freeze-dried wood chips in a tubular furnace and introduce nitrogen for 15 minutes before heat treatment to expel excess oxygen in the furnace. Then continue to introduce flowing nitrogen to protect the heat treatment at 200°C for 6 hours to remove the hemicellulose in the wood chips. After treatment, directly place it in a 3% acetic acid solution and shake and wash it at 60°C for 60 minutes to remove the soluble sugars remaining after the pyrolysis of the hemicellulose. Take out the sample and wash it again with deionized water until it is neutral;

[0028] (V) Pour the cleaned wood chips in (IV) into liquid nitrogen and freeze them for two hours, then place the frozen wood chips in a freeze dryer and freeze dry them for 24 hours before taking them out.

[0029] (VI) Weigh an appropriate amount of Fe(ClO4)3 and put it into 50mL of deionized water to fully dissolve; immerse the wood in (V) in the Fe(ClO4)3 solution for 20 minutes, then take it out and bake it in a vacuum oven at 40°C until there is no obvious water stain on the surface of the material; immerse the wood impregnated with Fe(ClO4)3 in a pyrrole solution dissolved in n-butanol, vacuum immerse it for 10 minutes, leave it for 10 minutes, then put it in a vacuum oven at 40°C and bake it until there is no obvious oil stain on the surface. Repeat the above steps four times, and cold press the sample at room temperature to form a wood aerogel-based / polypyrrole electrode material.

[0030] The electrical conductivity of the prepared wood aerogel-based electrode material is 86.49 S cm -1 , the specific capacitance is 192 F cm -3 , the cycle stability is 90% after 5000 cycles, and the energy density is 42.3wh kg -1 (59 Wh L -1 ), power density 45 kW L -1 (70kw kg -1 ).

[0031] Example 2

[0032] (I) Cut the wood into 1.5m long squares, and cut them into 2cm (length) × 2cm (width) × 1mm (thickness) wood chips along the cross section. Dry the wood chips at 100℃ until the moisture content is about 8%. Finally, put them in a climate chamber with a temperature of 25℃ and a relative humidity of 65% for equilibrium treatment.

[0033] (ii) Prepare a sodium chlorite solution with a mass fraction of 5%, add acetic acid dropwise into the solution, and adjust the pH of the solution to about 5. Then put the wood chips prepared in step (i) into the acidic sodium chlorite solution, stir thoroughly, and heat in a 75°C water bath for 1 h, replace with fresh solution, and repeat this process 5 times. After the reaction is completed, wash with deionized water until the pH value of the solution is neutral, and dry to a moisture content of 8% to remove lignin in the wood chips.

[0034] (iii) Pour the washed and neutralized wood chips in (ii) into liquid nitrogen and freeze them for two hours. Then put the wood chips frozen with liquid nitrogen into a freeze dryer and vacuum freeze-dry them for 24 hours before taking them out.

[0035] (IV) Place the freeze-dried wood chips in (III) into a tubular furnace and continuously flow nitrogen gas to heat the chips at 180°C for 4 hours to remove hemicellulose in the wood chips. After the treatment, place them directly in a 4% acetic acid solution and shake and wash them at 50°C for 70 minutes to remove the soluble sugars remaining after the pyrolysis of the hemicellulose. Take out the sample and wash it again with deionized water until it is neutral;

[0036] (V) Pour the cleaned wood chips in (IV) into liquid nitrogen and freeze them for two hours, then place the frozen wood chips in a freeze dryer and freeze dry them for 24 hours before taking them out.

[0037] (VI) Place the wood aerogel in the aniline mixed solution according to the mass ratio of wood aerogel: aniline: ethanol = 1:10:10, and vacuum impregnate for 2 hours; prepare 200ml 1mol / L HCl solution and stir in an ice bath; place the wood aerogel impregnated with aniline solution in a beaker. Dissolve ammonium persulfate in 25ml water (ammonium persulfate: aniline molar ratio is 1:1), add dropwise to the beaker (control the flow rate 4-5s per drop), and keep the system temperature below 5°C; continue the reaction for 6h to complete the polymerization of polyaniline, remove the wood chips loaded with polyaniline, wash with deionized water until neutral, and wash with ethanol to remove the unreacted aniline monomer and ammonium persulfate solution loaded on the surface. Freeze-dry the cleaned wood chips for 24 hours to obtain wood aerogel-based / polyaniline electrode materials.

[0038] The conductivity of the prepared wood aerogel-based electrode material is 85.47 S cm -1 , the specific capacitance is 159.6 F cm -3 , cycle stability after 5000 cycles is 95%, energy density is 41wh kg -1 (57 Wh L -1 ), power density 43 kW L -1 (68kw kg -1 ).

[0039] Example 3

[0040] 1. Cut a 1m long wood block into 2cm (length) × 2cm (width) × 3mm (thickness) wood chips along the cross section. Dry the wood chips at 100℃ until the moisture content is about 7%. Finally, place them in a climate chamber at 25℃ and 65% relative humidity for equilibrium treatment.

[0041] (ii) Prepare a sodium chlorite solution with a mass fraction of 5%, add acetic acid dropwise into the solution, and adjust the pH of the solution to 4.5. Then put the wood chips prepared in step (i) into the acidic sodium chlorite solution, stir thoroughly, and heat in a water bath at 80°C for 1 h, replace with fresh solution, and repeat this process 6 times. After the reaction is completed, wash with deionized water until the pH value of the solution is neutral, and dry to a moisture content of 7%, remove the lignin in the wood chips, and the wood will be white.

[0042] (iii) Pour the washed and neutralized wood chips in (ii) into liquid nitrogen and freeze them for two hours. Then put the wood chips frozen with liquid nitrogen into a freeze dryer and vacuum freeze-dry them for 24 hours before taking them out.

[0043] (IV) Place the freeze-dried wood chips in a tubular furnace, continuously introduce flowing nitrogen to exhaust excess oxygen in the tube, and then heat treat at 160°C for 6 hours to remove hemicellulose in the wood chips. After treatment, directly place in a 5% acetic acid solution and shake and wash at 55°C for 50 minutes to remove the soluble sugars remaining after the hemicellulose is pyrolyzed. Take out the sample and wash it again with deionized water until it is neutral;

[0044] (V) Place the washed wood chips into liquid nitrogen and freeze them for two hours. Then place the frozen wood chips into a freeze dryer and freeze dry them for 24 hours before taking them out.

[0045] (VI) Weigh 8.85g Fe(ClO4)3 and put it into 50mL deionized water to fully dissolve; soak the deionized wood aerogel / reduced graphene oxide composite material in the Fe(ClO4)3 solution for 20 minutes, take it out and bake it in a vacuum oven at 40℃ until there is no obvious water stain on the surface of the material; immerse the wood aerogel / reduced graphene oxide composite material impregnated with Fe(ClO4)3 in a pyrrole solution dissolved in n-butanol, vacuum immerse for 10 minutes, place it for 10 minutes, and then bake it in a vacuum oven at 40℃ until there is no obvious oil stain on the surface. Repeat the above steps for 3 times. And cold press at room temperature to form a wood aerogel-based / reduced graphene oxide / polypyrrole composite electrode material.

[0046] The conductivity of the prepared composite electrode material is 86.94 S cm -1 , the specific capacitance is 202 F cm -3 , cycle stability after 5000 cycles is 96%, energy density is 47wh kg -1 (63Wh L -1 ), power density 48 kW L -1 (74kw kg -1 ).

Claims

1. A method for preparing a hierarchical porous wood aerogel-based electrode material, characterized in that The steps include: (1) Cut the wood into wood chips with a thickness of 1 to 4 mm along the cross section and dry them evenly to a moisture content of 6 to 8%; (2) Vacuum immersing the dried wood chips in an acidic sodium chlorite solution to remove lignin from the wood chips and washing them to neutrality; (3) freezing the cleaned and neutralized wood chips with liquid nitrogen and then freeze-drying them; (4) heat treating the freeze-dried wood chips at 160-200°C for 2-6 hours to remove hemicellulose in the wood chips, then directly soaking them in an acetic acid solution to remove the soluble sugars remaining after the pyrolysis of the hemicellulose, and washing them to neutrality; (5) freezing the wood chips with liquid nitrogen again and then freeze-drying them to produce a hierarchical porous wood aerogel material; (6) The freeze-dried wood aerogel material is in situ polymerized in a pyrrole monomer using ferric chloride as an oxidant to prepare a hierarchical porous wood aerogel-based electrode material; or the freeze-dried wood aerogel material is immersed in an aniline monomer and in situ polymerized using hydrochloric acid as a dopant to prepare a hierarchical porous wood aerogel-based electrode material.

2. The method for preparing a hierarchical porous wood aerogel-based electrode material according to claim 1, characterized in that: After the wood chips are dried in step (1), they are placed in a climate chamber at a temperature of 25° C. and a relative humidity of 65% for equilibrium treatment.

3. The method for preparing a hierarchical porous wood aerogel-based electrode material according to claim 1, characterized in that: Step (2) specifically comprises vacuum impregnating the dried wood chips in a sodium chlorite solution with a pH value of 4.5-5 and a mass fraction of 4-8%, heating the solution to 70-80° C. in a water bath device, reacting the solution for 40-60 minutes, replacing the solution with fresh solution, repeating the process 6-8 times, and washing the wood chips with deionized water until the pH value reaches neutrality after the reaction to remove lignin from the wood chips.

4. The method for preparing a hierarchical porous wood aerogel-based electrode material according to claim 1, characterized in that: In steps (3) and (5), the liquid nitrogen freezing time is 2 h and the freeze-drying time is 24 h.

5. The method for preparing a hierarchical porous wood aerogel-based electrode material according to claim 1, characterized in that: Step (4) specifically comprises placing the freeze-dried wood chips in a tubular furnace and heating them under flowing nitrogen protection at 160-200° C. for 2-6 hours to remove hemicellulose in the wood chips, then directly placing them in a 3-5% acetic acid solution and shaking and washing them at 45-60° C. for 45-60 minutes to remove soluble sugars remaining after pyrolysis of the hemicellulose, taking out the sample, and washing them again with distilled water until they are neutral.

Citation Information

Patent Citations

  • Green separating process for components of lignocellulose

    CN105484083A

  • Anisotropic wood-based nanofiber aerogel and preparation method thereof

    CN109608685A